Aplikasi Metode Sukacita (Susun Angka Ciptakan Cerita) Dalam Pembelajaran Tematik Kelas 1 - Septiana Agustin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2019)
This study aims to apply innovative learning methods. New methods that are expected to provide references for teachers, especially low-class teachers. The method used in this study is a qualitative descriptive method. Data collection techniques are based on observations that cover several aspects. Observations are carried out in stages by comparing classes that apply the new method and those that do not. The data analysis technique is done by qualifying the observational data. The research results are shown based on observations by the teacher during the learning activities. There are differences when learning with the same material, but delivered by different methods. That is because the new method has several advantages, among others: children are more enthusiastic to play together, familiarize children with tolerance by not picking friends, class conditions more orderly, creating a pleasant atmosphere, and training children to work while learning in group dynamics.